Environmental Education - Center for Natural Resources; Jerry Culen; Martha Monroe (EDIS)
Environmental education (EE) is a discipline that helps create a citizenry that is knowledgeable, motivated and committed to taking appropriate action concerning environmental issues. Programs in EE should help individuals understand their interdependence with the environment, local ecosystems and other natural resources. Programs should foster awareness of critical environmental problems and issues, as well as opportunities to develop those skills needed to make informed decisions to protect and improve the environment. These programs include both youth and adult education efforts.